Plasma metabolomics reveals risk factors for lung adenocarcinoma - Yu, Mengjie; Wen, Wei; Wang, Yue; Shan, Xia; Yi, Xin; Zhu, Wei; Aa, Jiye; Wang, Guangji (Frontiers in Oncology, 2024)
To identify metabolites associated with lung adenocarcinoma (LUAD), we utilized gas chromatography-mass spectrometry (GC/MS) to detect metabolites in plasma samples from 670 LUAD, 135 benign lung nodules (BLN), and 278 healthy controls (HC). Odds ratios (OR) were calculated to identify LUAD risk factors and machine learning algorithms were used to distinguish between LUAD and BLN. High levels of oxalate, glycolate, glycine, glyceric acid, aminomalonic acid, and creatinine were identified as risk factors for LUAD (adjusted ORs>1.2, P<0.03). Remarkably, oxalate emerged as a distinctive metabolic risk factor exhibiting a strong correlation with the progression of LUAD (adjusted OR=5.107, P<0.001; advanced-stage vs. early-stage).The Random Forest (RF) model demonstrated a high degree of efficacy in distinguishing between LUAD and BLN (accuracy = 1.00 and 0.73, F1-score= 1.00 and 0.79, and AUC = 1.00 and 0.76 in the training and validation sets, respectively). TCGA and GTEx gene expression data have shown that lactate dehydrogenase A (LDHA), a crucial enzyme involved in oxalate metabolism, is increasingly expressed in the progression of LUAD. High LDHA expression levels in LUAD patients are also linked to poor prognoses (HR=1.66, 95% CI=1.34-2.07, P<0.001). In conclusion, our study reveals risk factors associated with LUAD.